Typology of recreational-tourism resources as an important element of the tourist offer - Mijalce Gjorgievski; Saso Kozuharov; Dejan Nakovski (UTMS Journal of Economics, 2013)
Tourism or the hospitality industry is among those economic activities that apart from realizing direct economic profits, it directly or indirectly impacts on the development of many other industries. Tourism through the tourist movements has a major impact on the geographical space, this effect is manifested on all the elements that make up the space, and these effects can be economic, social, public and environmental. Tourism consists of two basic components: Tourist movement and consumption, tourist movement is a basic spatial element while tourism consumption is the basic element of the tourism industry expressing the economic impact of tourism. Tourist movement necessarily initiate tourism consumption. In this context the question arises: what initiates tourist movement? The answer is: recreational-tourism resources are the main initiators for tourist travel and a very important tourist motive which animates the tourist movement. If the recreational-tourist resources are characterized by greater attractiveness better ambient and greater curiosity value, etc. this will initiate more massive tourist movement and greater tourist consumption. Therefore the necessity of defining, explaining, analyzing, and sharing recreational - tourism resources will be the key factors and subjects of analysis in this paper.
Keywords: Q26; 330; tourism; recreational resources; tourism resources; recreation need